Patient Work as a Maturing Approach Within HF/E: Moving Beyond Traditional Self-Management Applications. (September 2016) - Valdez, Rupa S.; Holden, Richard J.; Caine, Kelly; Madathil, Kapil; Mickelson, Robin; Lovett Novak, Laurie; Werner, Nicole
Over the last five years, human factors and ergonomics (HF/E) applications in healthcare have expanded beyond the institution to encompass the homes and communities of patients. The patient work approach has been developed as a means of formalizing the theoretical and methodological foundations of applying HF/E within this new domain. Early applications of the patient work approach were confined to studies of relatively straightforward self-management tasks. As the patient work approach matures, however, its application is spreading to more complex subdomains of health management in home and community settings. This panel will focus on cutting edge application and methodological areas of patient work. Each panelist will introduce their work, present challenges related to expanding the patient work approach in a new direction, and engage with audience members to address these challenges and brainstorm ways in which the patient work approach can be further adapted to more intricate healthcare challenges.